Capitalist Acumulation through Digital Platforms: From Click-farms to Dispossession of the Digital Commons (Global Journal of Human-Social Science, 2024)
The article analyzes several theoretical perspectives from the political economy of communication on the contribution of the activities of users and workers on digital platforms to capitalist accumulation. To this end, it addresses the transformation of crowdsourcing platforms into click farms and the commercial production of disinformation as opposed to the activity of ordinary users of social platforms. In this context, it proposes replacing the search for a particular update of the theory of digital labor and digital surplus value with an understanding of the Internet as a field in which different strategies of accumulation compete, linking the subsumption of intellectual labor to processes of accumulation through the dispossession of the general intellect. Finally, it points to the perspective of an algorithmic prince as a fundamental political condition for the maintenance and expansion of capitalist accumulation through digital platforms.
Keywords: surplus value platforms accumulation through dispossession digital labor Click farms